2020
DOI: 10.5902/1980509837279
|View full text |Cite
|
Sign up to set email alerts
|

Representação matemática do comportamento intra-anual do NDVI no Bioma Caatinga

Abstract: Os índices de vegetação obtidos por modelos, aplicados em imagens orbitais, são comumente utilizados para o monitoramento da cobertura do solo, sendo importantes para registrar alterações na biomassa, identificação do ciclo fenológico, relação com o sequestro de carbono e indicadores de mudanças climáticas. Na região do bioma Caatinga, a compreensão em escalas local e diária dos fenômenos que ocorrem na cobertura do solo é muito importante devido à sua heterogeneidade, sazonalidades e às múltiplas ações humana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Variations in rainfall distributions and volumes may have caused changes in vegetation cover, surface temperature, and evapotranspiration of the land portions observed in this study. Predominant vegetation of the Caatinga biome is quickly responsive to rainfall regimes, reducing foliage in the dry period (through deciduousness) and gaining biomass by the arrival of a new rainy period, which is considered a condition of defense and physiological adaptation of these highly efficient plants [102,103].…”
Section: Rainfall Variability In Land Cover Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in rainfall distributions and volumes may have caused changes in vegetation cover, surface temperature, and evapotranspiration of the land portions observed in this study. Predominant vegetation of the Caatinga biome is quickly responsive to rainfall regimes, reducing foliage in the dry period (through deciduousness) and gaining biomass by the arrival of a new rainy period, which is considered a condition of defense and physiological adaptation of these highly efficient plants [102,103].…”
Section: Rainfall Variability In Land Cover Classesmentioning
confidence: 99%
“…The first three imaging dates in the study showed that, on average, 52.26% of the territorial area of the region had 0 to 25% vegetation cover (Figure 6a-c), revealing the direct effects of low rainfall volumes resulting from the dry season on native vegetation. Under these conditions, variations in NDVI values are strongly linked to biomass production [102]. In studies carried out in the Caatinga, Cunha et al [22], Leivas et al [21], and Leivas et al [104] reported that monitoring large-scale variations of water indicators and vegetation status is of crucial importance to minimize the adverse effects of climate and land use changes on mixed agroecosystems.…”
Section: Vegetation Cover Indices Of the Municipalitymentioning
confidence: 99%
“…The imaging period (June) matches the rainy season, when there are a great herb layer and significant presence of vegetation leaf canopy, thus contributing to higher NDVI levels. Another important factor that should be considered in the Caatinga environment is the seasonal rainfall distribution, which plays a great role on the regional water balance, hence soil moisture content, thus directly influencing NDVI (Arraes et al, 2012;Silva Filho et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The biomass of the old stands, however, was lower than those of most other dry forests, which usually had more than 72 Mg ha −1 (Read and Lawrence 2003;Raherison and Grouzis 2005;Vargas et al 2008;Raharimalala et al 2012;Becknell and Powers 2014). Low water availability is the probable cause of the low biomass in Brazilian dry forests, the closest to the equator with the highest potential evapotranspiration (Silva Filho et al 2020). The biomass of the humid forests was within the ranges reported elsewhere (Fonseca et al 2011;Poorter et al 2016;Stas et al 2017) for both young (76 to 100 Mg ha −1 ) and old stands (100 to 334 Mg ha −1 ), except for the low biomass of the young stand of the montane forest.…”
Section: Biomass and Densitymentioning
confidence: 96%